2014
DOI: 10.1007/s11356-014-3919-z
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of antibiotic resistance genes in municipal wastewater by chlorination, ultraviolet, and ozonation disinfection

Abstract: This study investigated the inactivation of two antibiotic resistance genes (ARGs)-sul1 and tetG, and the integrase gene of class 1 integrons-intI1 by chlorination, ultraviolet (UV), and ozonation disinfection. Inactivation of sul1, tetG, and intI1 underwent increased doses of three disinfectors, and chlorine disinfection achieved more inactivation of ARGs and intI1 genes (chlorine dose of 160 mg/L with contact time of 120 min for 2.98-3.24 log reductions of ARGs) than UV irradiation (UV dose of 12,477 mJ/cm(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(74 citation statements)
references
References 30 publications
4
69
0
1
Order By: Relevance
“…The removal effi ciencies of tet genes by our CWs and those of the previous CWs are comparable to the removal effi ciencies of ARGs, such as tetG, by chlorination (3.24 log reductions), ultraviolet (2.48 log reductions), and ozonation (2.55 log reductions) processes 30) . The results clearly indicated that CWs appear to be an advanced treatment process to prevent the discharge of large amount of tet genes from the wastewater treatment plants.…”
Section: Removal Potential Of Tet Genes By Cwssupporting
confidence: 75%
“…The removal effi ciencies of tet genes by our CWs and those of the previous CWs are comparable to the removal effi ciencies of ARGs, such as tetG, by chlorination (3.24 log reductions), ultraviolet (2.48 log reductions), and ozonation (2.55 log reductions) processes 30) . The results clearly indicated that CWs appear to be an advanced treatment process to prevent the discharge of large amount of tet genes from the wastewater treatment plants.…”
Section: Removal Potential Of Tet Genes By Cwssupporting
confidence: 75%
“…Although advanced disinfection facilities can greatly reduce the danger of waterborne diseases (United States Environmental Protection and Agency, 2004), antibiotics and ARGs can still be released to the environment in disinfected effluents (Michael et al, 2013; Rizzo et al, 2013; Berkner et al, 2014; Carey and McNamara). Recent works report the improvement of disinfection in terms of ARG removal (Munir et al, 2011; McKinney and Pruden, 2012; Guo et al, 2013; Yuan et al, 2015; Zhuang et al, 2015). …”
mentioning
confidence: 99%
“…The majority of genes associated with this mechanism are dfr and sul genes which are both related to folic metabolism and are widespread in the environment, being predominantly located on plasmids or transposons 66 . It has been observed that the inactivation of ARGs such as sul1 from municipal wastewater is most effective with chlorination, followed by UV and ozonation 67 which could explain the infrequency of detection of these genes in Dis systems. Finally, genes associated with reduced permeability mechanism were only observed under the “loose” sequence similarity threshold for the NonDis samples and only constituted 0.21% of all detected AROs.…”
Section: Resultsmentioning
confidence: 99%